JOB INSECURITY, PERSON-ORGANIZATION FIT DAN OCB : PERAN MEDIASI JOB SATISFACTION PADA AUDITOR PEMERINTAH - Vika Arni Gupitasari; Adijati Utaminingsih; Hardani Widhiastuti (LPPM STIE Muhammadiah Bandung, 2025)
This study investigates the influence of job insecurity and person–organization fit on organizational citizenship behavior (OCB) through job satisfaction as a mediating variable. The low voluntary involvement of employees in organizational activities, which reflects a low level of OCB, is the driving factor behind this research. Auditors at the Representative Office of the Audit Board of the Republic of Indonesia (BPK) in Central Java Province, who are strategically assigned to ensure accountability in the management of state finances, serve as the subjects of this study. Structural Equation Modeling (SEM) based on AMOS version 23 was employed in this quantitative approach. A total of 198 employees were given questionnaires to collect data. The findings indicate that while person–organization fit significantly increases job satisfaction, job insecurity significantly reduces it. OCB is not directly influenced by either person–organization fit or job insecurity. On the other hand, the results demonstrate that job satisfaction has a positive effect on OCB and mediates the relationship between OCB and both person–organization fit as well as job insecurity. These findings highlight the importance of creating a workplace that enhances job satisfaction in order to motivate staff to engage in voluntary behavior.